Writing materiality into management and organization studies through and with Luce Irigaray - Fotaki, Marianna; Metcalfe, Beverly Dawn; Harding, Nancy (Human relations (New York), 2014)
There is increasing recognition in management and organization studies of the importance of materiality as an aspect of discourse, while the neglect of materiality in post-structuralist management and organization theory is currently the subject of much discussion. This article argues that this turn to materiality may further embed gender discrimination. We draw on Luce Irigaray’s work to highlight the dangers inherent in masculine discourses of materiality. We discuss Irigaray’s identification of how language and discourse elevate the masculine over the feminine so as to offer insights into ways of changing organizational language and discourses so that more beneficial, ethically-founded identities, relationships and practices can emerge. We thus stress a political intent that aims to liberate women and men from phallogocentrism. We finally take forward Irigaray’s ideas to develop a feminist écriture of/for organization studies that points towards ways of writing from the body. The article thus not only discusses how inequalities may be embedded within the material turn, but it also provides a strategy that enriches the possibilities of overcoming them from within.